(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the content and essence of scientifically based ideas presented by famous scientists who lived and worked in Uzbekistan at the first stage of the Renaissance, regarding the socio-economic life of society. In covering this topic, the author explored works related to the works of Burhanuddin Marghinani, Muhammad ibn Ali Hakim At-Termezi, Abu Isa Abdullah Muhammad ibn Isa At-Termezi. In the works of thinkers, attention was paid to private property of a person, social and economic issues, maturation of a person, his social activity, involvement in productive work.